Rola i postawa kadry kierowniczej w procesie radykalnych zmian (na przykładzie przedsiębiorstw regionu łódzkiego) - Zakrzewska-Bielawska, Agnieszka (The role and attitudes of the managers in the process of frame-breaking changes in Polish enterprises, 2006)
Different levels of managers, including top, middle and first-line managers act large role in the process of the frame-breaking changes. Representatives of this group initiate and prepare programmes of these changes. They are also responsible for their results. The attitudes and tasks of managers in the process of changes are discussed in this article. Results of own research referring to managers' attitudes, their advantages and losses and workers' participation in a process of the enterprises' frame-breaking changes are also presented in this paper.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 608-676